Novel anti-CEA affibody for rapid tumor-targeting and molecular imaging diagnosis in mice bearing gastrointestinal cancer cell lines - Shao, Huanyi; Lv, Kaiji; Wang, Pengfei; Jin, Jinji; Cai, Yiqi; Chen, Jun; Kamara, Saidu; Zhu, Shanli; Zhu, Guanbao; Zhang, Lifang (Frontiers in Microbiology, 2024)
Gastrointestinal cancer is a common malignant tumor with a high incidence worldwide. Despite continuous improvements in diagnosis and treatment strategies, the overall prognosis of gastrointestinal tumors remains poor. Carcinoembryonic antigen (CEA) is highly expressed in various cancers, especially in gastrointestinal cancers, making it a potential target for cancer. Therefore, the expression of CEA can reflect the existence of tumors and can be used as target for molecular imaging diagnosis and targeted therapy of gastrointestinal cancers. In this study, we report the selection and characterization of affibody molecules (Z CEA 539, Z CEA 546, Z CEA 919) specific to CEA protein. Their ability to bind to recombinant and native CEA protein have been confirmed by surface plasmon resonance (SPR), immunofluorescence and immunohistochemistry assays. Further, by using Dylight755-labeled Z CEA affibody showed accumulation within tumor site 0.5-hour post injection, and was continuously enhanced for 4 h. The Dylight755-labeled Z CEA affibody exhibited high tumor-targeting specificity in CEA+ xenograft-bearing mice, as well as possesses promising characteristics for tumor targeting imaging. Taken together, our results suggest the potential use of Z CEA affibodies as fluorescent molecular imaging probes for detecting CEA expression in gastrointestinal cancer.